1988
DOI: 10.1139/f88-135
|View full text |Cite
|
Sign up to set email alerts
|

Life History and Smolt-to-Adult Survival of Keogh River Steelhead Trout (Salmo gairdneri) and the Relationship to Smolt Size

Abstract: A decade of data on wild steelhead trout (Salmo gairdneri) from a coastal stream in British Columbia demonstrated large fluctuations in smolt number, age structure, size, estimates of adult run sizes, smolt-to-adult survival, and adult age. Adult runs averaged 922 (range 209–2730) with approximately 10% repeat spawning incidence. Females repeat spawned more than males and were more abundant as kelts, but maiden run adults were equally male and female. The proportion of males returning after 1, 2, and 3 yr in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
149
3

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(164 citation statements)
references
References 12 publications
12
149
3
Order By: Relevance
“…A number of studies (Bilton et al 1982;Bilton 1984;Ward and Slaney 1988;Martin and Wertheimer 1989;Ward et al 1989;Henderson and Cass 1991;Beckman et al 1998;Friedland et al 2009) have shown that larger juvenile Pacific salmon survive better in the early marine environment than smaller individuals. Throughout our study, hatchery fish were consistently larger than the better surviving wild chinook salmon.…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies (Bilton et al 1982;Bilton 1984;Ward and Slaney 1988;Martin and Wertheimer 1989;Ward et al 1989;Henderson and Cass 1991;Beckman et al 1998;Friedland et al 2009) have shown that larger juvenile Pacific salmon survive better in the early marine environment than smaller individuals. Throughout our study, hatchery fish were consistently larger than the better surviving wild chinook salmon.…”
Section: Discussionmentioning
confidence: 99%
“…During the same year we estimated 3,802 steelhead smolts with the SPIs based on 97% (95% CI: 91-97%) efficiency. Similarly, Ward and Slaney (1988) reported smolt abundance estimates of 5,543 from a comparable tributary in British Columbia. Many estimates of smolt abundance are highly variable from year to year, e.g.…”
Section: Survival and Recapture Probabilitiesmentioning
confidence: 90%
“…This was due to a general lack of data on the conditional status and demographics of resident O. mykiss, which made it difficult to evaluate the relative effects of individual condition and environment on population-scale life history patterns. Assessing environmental effects on sympatric resident and anadromous populations is challenging because of the great temporal variation in demographics over annual and decadal time scales (Ardren and Kapuscinski 2003;Savvaitova et al 2002;Shapovalov and Taft 1954;Ward and Slaney 1988). Nonetheless, such data are needed to fully understand the amount of life history variation within populations (McPhee et al 2014) and to improve predictive models .…”
Section: Limitations and Implicationsmentioning
confidence: 99%